Effectiveness of varicella vaccination during an outbreak in a large one-dose-vaccinated population in Shanghai. Issue 7 (30th December 2022) - Lin, Mingzhu; Wang, Qizhang; Deng, Pengfei; Xiao, Shaotan; Fei, Yi; Xue, Caoyi
ABSTRACT: Emergency vaccination (EV) is used as effective postexposure prophylaxis (PEP) to control varicella outbreaks within 3–5 days. However, the advantages of a second dose of varicella vaccine (VarV) in students who had received one dose before an outbreak and the potential benefits of EV at more than 5 days after exposure have not been fully evaluated. This study evaluated the vaccine effectiveness (VE) of EV in preventing disease development during a varicella outbreak in Shanghai, China, in 2020. Questionnaires were used to obtain student demographic information, clinical manifestations, varicella history, vaccination status, and willingness to receive EV. The VE of EV was calculated as [1-relative risk (RR)] ×100%. Among the 1455 students included in this study, 31 cases were identified, resulting in an overall attack rate of 2.13%. There were 6 cases in unvaccinated students and 25 cases in one-dose-vaccinated students. A total of 788 students received one EV dose. The attack rates were 6.38% (6/94), 4.26% (19/446), 2.82% (2/71), and 0.56% (4/717) among unvaccinated students, students who received 1 dose of VarV, and students who received EV with the 1 st and 2 nd dose of VarV, respectively. Compared to that in unvaccinated students, the VE of EV with the 2 nd dose of VarV was 88% (95% CI 49% to 97%). EV should be performed as soon as possible after exposure. Nevertheless, vaccination is still recommended at more than 5 days post exposure to control varicella outbreaks.